2011
DOI: 10.1177/0034355211404567
|View full text |Cite
|
Sign up to set email alerts
|

Gender Effect According to Item Directionality on the Perceived Stress Scale for Adults With Multiple Sclerosis

Abstract: Assessment is critical to rehabilitation practice and research, and self-reports are a commonly used form of assessment. This study examines a gender effect according to item wording on the Perceived Stress Scale for adults with multiple sclerosis. Past studies have demonstrated two-factor solutions on this scale and other scales measuring stress-related constructs with factor loadings being determined by item wording. Moreover, women have typically scored higher on these measured constructs. However, a litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 58 publications
5
32
1
Order By: Relevance
“…The PSS has been utilized in numerous studies as a self‐report measure of perceived stress in a variety of fields since its development (see Gitchel, Roessler, and Turner, : 22 for a review). It has been used in a wide range of settings with general and clinical populations to demonstrate acceptable psychometric properties for evaluating perceived stress (see Remor, : 87 for a review), associations with established measures of anxiety, stress, coping, depression, and other physiological responses (for reviews, see Örücü and Demir, : 104; Mimura and Griffiths, : 380).…”
Section: The Perceived Stress Scalementioning
confidence: 99%
See 3 more Smart Citations
“…The PSS has been utilized in numerous studies as a self‐report measure of perceived stress in a variety of fields since its development (see Gitchel, Roessler, and Turner, : 22 for a review). It has been used in a wide range of settings with general and clinical populations to demonstrate acceptable psychometric properties for evaluating perceived stress (see Remor, : 87 for a review), associations with established measures of anxiety, stress, coping, depression, and other physiological responses (for reviews, see Örücü and Demir, : 104; Mimura and Griffiths, : 380).…”
Section: The Perceived Stress Scalementioning
confidence: 99%
“…Gitchel et al. (: 21) note that multiple studies using disparate sample populations have consistently shown that the PSS items load on two factors: the negatively worded items loading on one and the positively worded items on the other . Previous researchers have attached various labels to these factors such as General Distress and Ability to Cope (Hewitt, Fleck, and Mosher, ), and Perceived Helplessness and Perceived Self‐Efficacy (Roberti, Harrington, and Storch, ).…”
Section: The Perceived Stress Scalementioning
confidence: 99%
See 2 more Smart Citations
“…According to previous studies, females have consistently higher PSS scores. This was attributed to negatively scored items in the PSS; females often score higher and subjectively experience more stress than males and show a greater worry-disposition (39,(44)(45)(46)(47)(48)(49). However, nurses, who had experienced presenteeism, had a statistically significant higher PSS score (21.42).…”
Section: Discussionmentioning
confidence: 99%